Wayfinding for all : case study Malaysian public health service clinic - Tahirah Zahirah binti Azman (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2019)
Wayfinding system plays a very crucial part in a complex design environment. This is especially evident in the environment of healthcare sector where various medical departments are located. The various types of users such as patients, visitors, and staff that visit the healthcare sector also need to be considered where they will be consist of people with disabilities and elderly that needs special elements in wayfinding system that help them navigate through the complex environment. This research aim to develop and recommends best practice for wayfinding for all as a set of tools for design practice in a public primary health clinic. The research methods and strategy that are applied are content analysis and case studies that will consist of evaluation through observation, access audit questionnaires and interview. Objectives of this research are (i) to assess the level of accessibility of existing facilities for PwDs and elderly as well as to identify levels of wayfinding in existing primary healthcare environment, (ii) to identify the relationship between levels of accessibility, level of wayfinding and wayfinding performance, and finally (iii) to identify different elements of wayfinding and to suggest wayfinding guidelines for all as a set of tool for design practice in primary health care environment. Firstly, through a rigorous literature review on wayfinding and wayfinding for PwDs, wayfinding design aspects for PwDs were identified. Secondly, based on existing knowledge of wayfinding and healthcare environment, wayfinding design parameters that are related to enabling wayfinding environment to PwDs will be developed. Thirdly, four evaluation tools; Universal Design Environment Assessment (UDEA), Wayfinding Environment Assessment (WEA), Wayfinding Design Parameter Rating Scale (WPRS), and Wayfinding Performance Assessment (WPA) are applied. Fourthly, previously identified wayfinding design parameters are further evaluated using Wayfinding Design Parameter Rating Scale (WDRS) by the users for their relevance. Finally, based on the findings, wayfinding guidelines for all, as a set of tools for design practice are developed to aid the architects and designer. Then study of the performance of the user using Wayfinding Performance Assessment (WPA) in relation to Universal Design Environment Assessment (UDEA), and Wayfinding Environment Assessment (WEA) are studied in each case study. The sample sizes collected for WPRS and WPA is 58 and 143 respondents respectively. The research led to the new findings on the existing situation of wayfinding in the Malaysian public health clinic, its improvement and effective wayfinding that fit for all. The case studies that are studied in this research are Klinik Kesihatan Presint 9 and Klinik Kesihatan Presint 18. Limitations of the research are limited time, finance, and human resources for research as well as research in the scope of Malaysian public health clinic. This research offer relevant information to wayfinding for all that can lead to improved user satisfaction, safety and user flow in Malaysian public health clinic. The suggested wayfinding design model has practical implications for architects and designers and offer some suggestions and possible solution, which act as tools for site design and building design of an inclusive primary healthcare environment.